Globus pharyngeus and extraesophageal reflux: simultaneous pH <4.0 and pH <5.0 analysis - Zeleník, Karol; Matoušek, Petr; Urban, Ondřej; Schwarz, Pavel; Stárek, Ivo; Komínek, Pavel (The Laryngoscope, 2010)
OBJECTIVES/HYPOTHESIS: Weakly acid refluxes seem to play an important role in the pathogenesis of extraesophageal reflux. The aim of this study was to evaluate how proportional representation of patients with extraesophageal reflux in a group of patients with globus pharyngeus changes when we use both pH <4.0 as well as pH <5.0 as a pathological threshold for an extraesophageal reflux episode. STUDY DESIGN: Prospective pH monitoring study of 46 patients. METHODS: Patients with pure globus pharyngeus lasting more than 3 months were included in the study. The pH monitoring was performed (Smit technique) with double probes (fixed distance of 15 cm). The recorded data using only pH <4.0 and using both pH <4.0 along with pH <5.0 as thresholds for extraesophageal reflux episode were analyzed simultaneously. The reflux area index 4 >6.3 and reflux area index 5 >72.6 were considered as clear pathological extraesophageal reflux. RESULTS: Extraesophageal reflux was proven in 23.9% patients with pure globus pharyngeus when standard analysis using only pH <4.0 was used as pathological threshold. If both pH <4.0 and pH <5.0 were used as the pathological threshold, clear extraesophageal reflux was found in four more (8.7%) patients. CONCLUSIONS: This study indicates the possible role of weakly acid extraesophageal reflux episodes in some patients with globus pharyngeus. Other studies on this issue, including the use of biological markers such as signs of inflammation, are warranted.
Keywords: výsledek terapie; lanzoprazol; hodnocení rizik; 2-pyridinyl methylsulfinyl benzimidazoly; Male; kohortové studie; Risk Assessment; Cohort Studies; následné studie; sexuální faktory; Adult; Age Factors; Hydrogen-Ion Concentration; Prospective Studies; dospělí; mužské pohlaví; Laryngopharyngeal Reflux; Severity of Illness Index; 2-Pyridinylmethylsulfinylbenzimidazoles; Follow-Up Studies; koncentrace vodíkových iontů; monitorování fyziologických funkcí; Treatment Outcome; manometrie; Manometry; lidé; Monitoring, Physiologic; ženské pohlaví; Humans; Body Mass Index; Sex Factors; věkové faktory; Gastric Acidity Determination; index tělesné hmotnosti; Lansoprazole; stanovení žaludeční acidity; stupeň závažnosti nemoci; laryngofaryngeální reflux; Female; lidé středního věku; Middle Aged; prospektivní studie